Evaluation of Elastographic techniques generated by means of external vibration - Arroyo Barboza, Johnny Junior (2017)
Breast cancer is one of the greatest problems of national and international public health, whose incidence among women population shows an increasing trend. Nowadays there are several elastographic techniques, which seek to characterize the tissue, that is, to analyze the response produced by the application of a perturbation in the medium, to describe its mechanical properties. Among the modalities used are ultrasound, nuclear magnetic resonance and optical coherence tomography. On the other hand, among the types of disturbance used are low frequency mechanical waves, a uniform compression force or acoustic radiation force. In this thesis work, ultrasound was used due to its low economical cost in comparison to the other modalities.